The University of Notre Dame : a history - Blantz, Thomas E. (University of Notre Dame Press, 2020)
"Thomas Blantz's monumental The University of Notre Dame: A History tells the story of the renowned Catholic university's growth and development from a primitive grade school and high school founded in 1842 by the Congregation of Holy Cross in the wilds of northern Indiana to the acclaimed undergraduate and research institution it became by the early twenty-first century. Its growth was not always smooth -- slowed at times by wars, financial challenges, fires, and illnesses. It is the story both of a successful institution and of the men and women who made it so ..."--Publisher note